Participatory variety selection of okra (Abelmoschus esculentus L.) genotyes for adaptation to the semi-arid agro-ecology of northern Ghana - Sugri, I.; Abdulai, M.S.; Larbi, Asamoah; Hoeschle-Zeledon, Irmgard; Kusi, F.; Agyare, R.Y. (Academic Journals, 2015)
In a two-year study, participatory variety selection (PVS) was employed to evaluate the performance of 19 okra (Abelmoschus esculentus L.) c. v. Moench genotypes in a semi-arid agro-ecology in northern Ghana. The PVS sessions were organized at 65, 80 and 95 days after planting for 272 farmers to select the most preferred genotypes base on plant growth, maturity period and yield components. Results of this study indicate high significant differences among the genotypes (P< 0.0001) for most essential agronomic yield traits evaluated. Five most recurring preference traits were high fruit yield, early maturing, multiple harvest frequency, drying quality and long tender-life. Glabrous leaf, stem and fruit were important to farmers because most of the production operations are still being manually done. Genotypes with high potential included: NOKH 1004 (9.55 ton\ha), FV-Unn-manna (5.85 ton\ha), NOHK 1003 (5.17 ton\ha), NOKH 1002 (2.83 ton\ha), FV-Kpazeya (2.83 ton\ha), TZ-SMN-86 (2.30 ton\ha), AAK (2.11 ton\ha), NB-55-Srivan (1.98 ton\ha), Sasilon (1.70 ton\ha), FV-Unn (2.20 ton\ha) and Ex-Makutopora (1.27 ton\ha). Genotypes Sasilon, NOKH-1004, NB-55-Srivan and NOKH-1003 recorded the highest ranking among farmers during the PVS. High yielding and early maturing genotypes which are amendable to drying may show wide adoption rate due to the premium on dehydrated okra. These genotypes can be suggested as candidates for inspection by the National Variety Release and Technical Committee for release to farmers to increase access to improved okra varieties.